Natural resource-based conflicts in rural Zimbabwe - Matanzima, Joshua; Chadambuka, Patience; Helliker, Kirk (New York : Routledge, 2024)
"This book investigates the range of conflicts over land and other natural resources in contemporary Zimbabwe, considering the different forms these conflicts take, and the ensuing outcomes. Zimbabwe is a country rich in natural resources, including land, wildlife, minerals, and water resources. These resources are integral to the formal and informal livelihoods of most Zimbabweans, as well as supporting many key industries. Wildlife, land, and water resources are also embedded in indigenous knowledge systems, religious beliefs and rituals in many rural communities, forming an important part of people's identity and sense of belonging. However, this book demonstrates the ways in which rural communities are being denied access to these resources and being displaced by extractive companies and by the government. Their response is often to turn to violence to try to reclaim their lands. Drawing on original empirical research from different conflicts across Zimbabwe, the book also considers the issue in the context of problems such as climate change, human wildlife conflicts, and politico-economic crises. This book will be useful to policy makers, students, conservationists, and academics across the fields of sociology, human geography, development, political science, and environment studies"--
Natural Resource-Based Conflicts in Zimbabwe / Joshua Matanzima, Patience Chadambuka and Kirk Helliker -- Part A: Land, Natural Resources and Conflict -- Domestic Communal Land Grabbing and Dwindling Peri-Urban Spaces: The Case of Midlands District's Mataga Communal Areas / Patience Chadambuka, Talent Moyo, Faith Zengeni and Praise Percy Tinashe Gandah -- Natural Resource Conflicts in Western Zimbabwe / Robert K. Hitchcock, Melinda C. Kelly and Maria Sapignoli -- Othering Doma Foragers: Contestations Over Natural Resources in the Mid-Zambezi Valley / Vincent Jani, Nigel L. Webb and Anton H. de Wit -- Women's Land Access and Gendered Land Conflicts in Hwedza and Makoni Districts / Ngonidzashe Chidavaenzi and Chengetai E. Hamadziripi -- Resource Conflicts in Chiredzi District: The Case of the Minority Hlengwe against Settlers and the State, 1950s-2022 / Taderera Hebert Chisi -- Part B: Water and Conflict -- Water as a Site of Contestation at Lake Kariba / Joshua Matanzima -- Conflicts over River Sand Use and Management in Binga District / Christopher Mweembe -- Conflict over Land and Water Resources in Zimunya, Manicaland Province / Aldrin T. Magaya and Mathew Ruguwa -- Whose Water is it? Underground Water and Social Conflicts in Fuleche, Hurungwe District, c1958-2020 / Ivan Marowa -- Governance, Power Dynamics and Conflicts in Norton's Small-Scale Fisheries / Tawanda Jimu, Martin Magidi and Simbarashe Gukurume -- Conflicts over Natural Resources at Mutirikwi Dam in Masvingo Province / Shumirai Nyota and Jeriphanos Makaye -- Part C: Minerals and Conflict -- Farmer-Miner Conflicts in Mberengwa North, 2000-2020 / Praise Percy Tinashe Gandah -- Mining-Induced Displacement and Resource Conflicts in Chiadzwa / Simbarashe Gukurume, Felix Tombindo and Tawanda Jimu -- Farming-Mining Conflicts surrounding Land Use on A1 Farms in Shurugwi District / Tendai Nciizah -- Conflicts over Harnessing of Diamond Resources in Marange Communal Area, Eastern Zimbabwe, 2006 -- 2015 / Mathew Ruguwa.
Keywords: Natural resources -- Zimbabwe; Land use, Rural -- Zimbabwe; Water-supply -- Zimbabwe; Mines and mineral resources -- Zimbabwe; Social conflict -- Zimbabwe; SOCIAL SCIENCE / Sociology / Rural; SOCIAL SCIENCE / Violence in Society